Kecakapan Kultural Konselor Dalam Praktek Bimbingan Dan Konseling - Pranowo, Taufik Agung; Permana, Septian Aji (Universitas Muhammadiyah Metro, 2024)
The aims of this study are 1) the level of analysis of cultural counselors' abilities in guidance and counseling practices and 2) the analysis of factors influencing the involvement of cultural counselors in guidance and counseling practices. This research method is a survey method. The targets in this study were the MGBK SMA Sleman Yogyakarta District, which consisted of 64 counseling teachers. The research procedures carried out in this study were 1) sample identification, 2) questionnaire development, 3) research implementation, 4) data collection, 5) data analysis, and 6) interpretation and conclusion. The data collection instrument used a cultural distribution questionnaire. Data analysis in this study is 1) descriptive analysis, 2) inferential analysis, 3) regression analysis. The results of this study show that the F-value is 4.56 with a p-value of 0.005. Because the p-value is less than 0.05, it can be concluded that there is a significant difference between the components of cultural ability measured in this study. In addition, it is known that the three components of cultural ability significantly influence the effectiveness of guidance and counseling practices. Cultural awareness had the most significant influence (β = 0.29, p = 0.011), followed by cultural skills (β = 0.26, p = 0.019) and cultural knowledge (β = 0.23, p = 0.022). Cultural attitudes have no significant effect (β = 0.20, p = 0.065). Counselors' cultural skills in guidance and counseling practice at MGBK SMA Sleman Regency, Yogyakarta, are critical to understanding and responding to students' needs in the local cultural context. The main aspects of the counselor's cultural skills are understanding local culture, sensitivity to local context, use of language and culturally relevant terms, collaboration with cultural stakeholders, and self-development.